Differential alteration of rumen microbial composition in response to 3-nitrooxypropanol supplementation in dairy cattle fed high-grain and high-forage diets - Y. Choi; M. Zhou; Y. Ban; M. Oba; S. Duval; L.L. Guan (Journal of Dairy Science)
ABSTRACT: Although 3-nitrooxypropanol (3-NOP) is known to effectively reduce methane (CH4) emissions in ruminants, its effect on rumen microbial communities under different dietary composition remains less understood. This study investigated how different diet compositions with 3-NOP supplementation affected rumen microbial communities in dairy cows. Rumen samples were obtained from 2 previous studies: a crossover design study with two 3-NOP levels (0 and 130 mg/kg DM) under a high-grain diet (HG; grain:forage = 60:40, n = 12), and a 3 × 3 Latin square design study with three 3-NOP levels (0, 68, and 132 mg/kg DM) under a high-forage diet (HF; grain:forage = 40:60, n = 15). A total of 138 rumen samples (HG: 48 and HF: 90 samples) were subjected to metataxonomic analysis to identify the compositional shifts of rumen microbiota (bacteria, archaea, and protozoa) in response to 3-NOP supplementation. The ruminal bacterial response to 3-NOP was more pronounced under HG diet (11 genera affected) than under HF diet (2 genera affected), with Lachnospiraceae NK3A20 group consistently increased under both diets. This bacterial group showed diet-specific fermentation patterns, correlating with increased molar proportion of butyrate under HF diet and potentially contributing to increased molar proportion of propionate under HG diet through succinate production. Methanogen responses to 3-NOP supplementation were also diet-dependent. Methanosphaera sp. increased under both diets, however, distinctive changes including contrasting responses between Methanobrevibacter gottschalkii and Methanobrevibacter ruminantium under HF diet were seen, reflecting their different metabolic capabilities in substrate utilization for methanogenesis in response to 3-NOP. Notably, ruminal Mbb. gottschalkii (H2-dependent) decreased, whereas Mbb. ruminantium (H2/formate-dependent) increased under HF diet, suggesting potential adaptation mechanisms to 3-NOP-induced changes in substrate availability. Ruminal protozoal communities remained unaffected under both diets. Further analysis of combined 2 studies with a batch effect correction approach revealed increases in Lachnospiraceae NK3A20 group, Saccharofermentans, Mbb. ruminantium, and Methanosphaera sp. group 5 and ISO3-F5, and decreases in Mbb. gottschalkii and Methanomassiliicoccaceae group 4 sp. MpT1 under 3-NOP supplementation. These findings demonstrate that 3-NOP has consistent effects on specific microbial taxa regardless of diet composition, and it also has diet-dependent effects on other members of the rumen microbiota. This knowledge provides valuable insights for optimizing CH4 mitigation strategies in dairy production systems under different dietary compositions.